A prospective, up-down sequential allocation study investigating the effectiveness of vital capacity breaths using high-flow nasal oxygenation versus a tight-fitting face mask to pre-oxygenate term pregnant women. (February 2021) - Al-Sulttan, S.; Bampoe, S.; Howle, R.; Setty, T.; Columb, M.; Patel, A.; Fernando, R.; Husain, T.; Sultan, P.
Highlights: Pre-oxygenation using high-flow nasal oxygen (HFNO) in term, non-labouring women. HFNO did not reliably achieve ET O2 fraction ≥0.90 in 20 vital capacity breaths. Standard face mask pre-oxygenation outperformed HFNO in reaching FET O2 ≥0.90. Closed-mouth, HFNO does not outperform open mouth pre-oxygenation. Abstract: Background: The role of high flow nasal oxygenation (HFNO) for pre-oxygenation before obstetric general anaesthesia remains unclear. This study aimed to determine the number of vital capacity breaths using HFNO required to pre-oxygenate 90% of parturients to an end-tidal oxygen concentration fraction (FET O2 ) of ≥0.90 (termed EN90). Methods: Using up-down, sequential allocation trial design, volunteer term parturients undergoing caesarean delivery were investigated with HFNO with their mouth closed, followed by mouth open, and if FET O2 ≥0.90 was not achieved after a maximum of 20 vital capacity breaths, pre-oxygenation was attempted with a face mask. The primary outcome was the number of vital capacity breaths required using HFNO (mouth open and closed) to achieve EN90. Secondary outcomes included assessment of EN90 using mouth open versus mouth closed and face mask pre-oxygenation, maternal satisfaction and evaluation of fetal cardiotocography. Results: Twenty women at term were recruited. Successful pre-oxygenation occurred in 4 (20%), 3 (15%) and 14 (70%) women with HFNO mouth closed, HFNO mouth open, and via face mask respectively. At up to 20 vital capacity breaths, face mask pre-oxygenation was more successful at achieving EN90 compared with both HFNO with a closed ( P =0.006) or open ( P =0.001) mouth. Closed mouth HFNO did not outperform open mouth pre-oxygenation. Conclusion: Face mask pre-oxygenation is more effective at achieving EN90 compared with to HFNO within a clinically acceptable number of vital capacity breaths. Further studies are needed to determine the role of HFNO in optimising the time before desaturation and for apnoeic oxygenation in term parturients.